2010
DOI: 10.4028/www.scientific.net/jera.1.57
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Load Capacity of Finite Slider Bearings with Slip Surfaces and Stokesian Couple Stress Fluids

Abstract: A mathematical model for the hydrodynamic lubrication of finite slider bearings with velocity slip and couple stress lubricants is presented. A numerical solution for the mathematical model using finite element scheme is obtained using four node linearly interpolated quadrilateral elements. Stiffness integrals obtained from the weak form of the governing equations were solved using Gauss Quadrature to obtain a finite number of stiffness matrices. The global system of equations was obtained for the bearing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The use of slider bearing has been proved to be very useful from the industry point of view for many decades. This has been documented in the literature (Agrawal (1986), Lin (2001), Deheri et al (2005), Ahmad and Singh (2007), Oladeinde and Akpobi (2010), Deheri and Patel (2011), Deheri (2013, 2015)). The basic phenomenon associated with hydrodynamic slider bearing is the formation of a converging wedge of the lubricant.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…The use of slider bearing has been proved to be very useful from the industry point of view for many decades. This has been documented in the literature (Agrawal (1986), Lin (2001), Deheri et al (2005), Ahmad and Singh (2007), Oladeinde and Akpobi (2010), Deheri and Patel (2011), Deheri (2013, 2015)). The basic phenomenon associated with hydrodynamic slider bearing is the formation of a converging wedge of the lubricant.…”
Section: Introductionmentioning
confidence: 53%
“…From equation 13, one can notice that the load carrying capacity enhances by 0.98254 μ * L ̅ B ̅ due to the magnetic fluid lubrication as compared to conventional fluid based bearing system. Eventually, as found, this is much more than the case of constant viscosity (Agrawal (1986), Lin (2001), Ahmad and Singh (2007), Oladeinde and Akpobi (2010), Deheri and Patel (2011), Patel and Deheri (2015)) One can find the graphical representations of load bearing capacity of the short bearing in Fig. 2-11.…”
Section: Resultsmentioning
confidence: 80%
“…With the help of equations ( 1) and ( 2) and the following dimensionless variable and parameters Equation ( 6) becomes where and The corresponding boundary conditions are Solving equation (7) with boundary conditions (9), the nondimensional pressure distribution is obtained as (5)…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Rao and Prasad [15] studied the effect of velocity-slip and viscosity variation on journal bearings and found that the load carrying capacity of the bearing was less when slip was present also, friction decreased with viscosity. Oladeinde and Akpobi [16] investigated the load capacity of slider bearings with slip surfaces and couple-stress fluids. The finite element method was used and it was concluded that the couple-stress parameter causes an increase in the load capacity and to achieve maximum load the slip-velocity must attain some minimum value.…”
Section: Introductionmentioning
confidence: 99%